The Use and abuse of nature - Gadgil, Madhav; Guha, Ramachandra (New Delhi Oxford University, 2000)
This book is in two parts.The first is 'This Fissuredland' presents on interpretative ecological history of the subcontinent.The focus is on the use and abuse of forest resources and the second part is 'Ecology and equity is a spirited intervention into t
Incorporating this fissured land, an ecological history of India and ecology and equity
Keywords: Nature; Human beings; Human ecology